Delta—fast ripple coupling suppression: designing a brain-mimetic stimulation paradigm for seizure abolishment - Tufa, Uilki; Dian, Joshua A.; Zahra, Anya; Wu, Chiping; Zhang, Liang; Carlen, Peter L.; Bardakjian, Berj L. (Frontiers in Neuroscience, 2025)
Deep brain stimulation can be an effective alternative treatment for patients that are intractable to antiseizure medication and do not meet surgical inclusion criteria. Clinical trials have demonstrated the safety of thalamic stimulation using a high frequency stimulus but with limited efficacy. Our group has previously shown, in silico, the success of stimulation with a brain-mimetic therapeutic poly-rhythmic signal, outperforming mono-rhythmic waveforms. In this study we extend our findings to an in vivo model and investigate a thalamic continuous stimulation paradigm using a brain-mimetic signal, where the amplitude of a high frequency rhythm is modulated by the phase of a low frequency rhythm forming a phase-amplitude coupled (PAC) waveform, to suppress seizure-like events (SLEs) in a hippocampal-kindled mouse model. We aim to show that application of our proposed “Dithered Effective Phase-Amplitude Coupled Electrical Rhythmic Stimulation (DEPACERS)” is more effective in seizure control than mono-rhythmic stimulation. Bipolar electrodes were implanted in the CA3 of the hippocampus and in the contralateral medial dorsal nucleus of the thalamus, allowing for stimulation and iEEG recordings. Video analysis was used for assessment of animal motor behavior. Mice were kindled daily through unilateral CA3 stimulations reaching evoked convulsive SLEs, then spontaneous recurrent seizures. To test suppression in fully kindled mice, thalamic stimulation using a PAC waveform was applied continuously for 15 min, followed by hippocampal stimulation to evoke an SLE. We found a 1 Hz–100 Hz phase-amplitude PAC waveform to be effective in suppressing SLEs (confirmed by iEEG and video analysis) and increasing kindling threshold. Low frequency and interictal spike suppression following interictal stimulus administration was found as a marker to assess the effective stimulus parameters. DEPACERS outperformed mono-rhythmic stimuli in evoked SLEs. These findings are important in the development of novel brain stimulation strategies for epileptic patients.